Characterization of Pleurotus citrinopileatus hydrolysates obtained from Actinomucor elegans proteases compared with that by commercial proteases. Issue 9 (17th August 2022) - Zhang, Weiwei; Shi, Kexin; Han, Yaqian; Wang, Jianming; Yang, Chen; Xu, Xu; Li, Bingye
Abstract : Abstract: Pleurotus citrinopileatus, a nutritious and palatable edible mushroom, can be used as an appropriate material to prepare high‐grade flavoring agents. Based on this, the current study aimed to investigate the feasibility of a productive protease system from Actinomucor elegans to prepare P. citrinopileatus hydrolysate (PCH). The Actinomucor elegans crude protease (AECP) was prepared from the solid‐state fermentation product of P. citrinopileatus by A. elegans . AECP and four commercial proteases (alcalase, neutrase, papain, and protamex) were applied to acquire five kinds of PCHs. The physical‐chemical properties of PCHs as well as its concentration and composition of nonvolatile compounds were comparatively analyzed. Sensory evaluation and electronic tongue analysis were utilized to evaluate sensory characteristics. AECP was found to be the most effective protease, with the highest hydrolysis degree (35.91%) and protein recovery (81.46%). The result of molecular weight distribution indicated that peptides below 500 Da were the main fraction of AECP hydrolysates, while AECP hydrolysates showed the highest content of monosodium glutamate‐like (20.23 ± 0.16 mg/g) and flavor 5′‐nucleotide (4.30 ± 0.07 mg/g) peptides. In summary, the AECP hydrolysate had superior sensory profiles compared with other hydrolysates. In addition, AECP hydrolysates exhibited favorable kokumi taste in which peptides below 500 Da showed the highest correlation with kokumi by the results of partial least‐squares regression. These results indicated the feasibility of applying PCHs as flavor additives or seasoning in the food industry. AECP might be used as an alternative enzyme choice because of its low cost and high hydrolysis efficiency. Practical Application: Pleurotus citrinopileatus served as a potential raw material for natural seasonings because of its high protein content and appropriate ratio of umami amino acids to total amino acids. Enzymatic hydrolysis was an efficient approach to improve the flavor of P. citrinopileatus, where the choice of enzyme was one of the most critical factors. The research indicated that P. citrinopileatus hydrolysate prepared by A. elegans crude protease (AECP) exhibited an acceptable flavor, which provided theoretical support for the high‐value utilization of P. citrinopileatus as food seasoning. AECP might be applied as an alternative enzyme resource because of its low cost and high hydrolysis efficiency.